The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2174/0929867323666160112122858
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dissection of Renal Ischemia-Reperfusion: Oxidative Stress and Cellular Events

Abstract: Ischemic reperfusion kidney injury (IRKI) is a complex pathophysiological event, which is the most common cause of the acute kidney injury. The key characteristic of IRKI is a reduction in glomerular filtration rate, which implies an underlying impairment in hemodynamic regulation. In recent decades, convincing evidence illuminated the molecular and pathological events in the acute kidney injury, revealing the role of ischemia/reperfusion, oxidative stress, apoptosis, inflammation, fibrosis and changes in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 0 publications
3
54
0
2
Order By: Relevance
“…Recently, miRNAs have been involved in the cell response to I/R in kidney30. Related to this, here we demonstrated that in vivo HIF-1α interference leads to a lower expression of miR-127-3p and, consequently, increased expression of its target gene Bcl6, a transcriptional repressor involved in apoptosis31 and survival regulation32.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, miRNAs have been involved in the cell response to I/R in kidney30. Related to this, here we demonstrated that in vivo HIF-1α interference leads to a lower expression of miR-127-3p and, consequently, increased expression of its target gene Bcl6, a transcriptional repressor involved in apoptosis31 and survival regulation32.…”
Section: Discussionsupporting
confidence: 72%
“…In oxygen deprivation, anaerobic glycolysis is enhanced, lactic acid is accumulated, mitochondrial dysfunction is enhanced, and production of ROS and superoxide is upregulated [53]. The injury expands after reperfusion that is characterized by inflammatory response with leukocyte and complements activation that progresses to an oxidant environment that cannot be counterbalanced by antioxidant mechanisms [54] and uneventfully leads to excessive cell death [53]. …”
Section: Introductionmentioning
confidence: 99%
“…1 The damage is further complicated by the release of oxygen-derived free radicals into the tissue, although reperfusion is necessary for ischemic tissue survival. 2 Renal ischemia-reperfusion (R-IR) injury may be resulted in due to renal transplantation, shock, sepsis and surgical procedures despite great clinical efforts. 3 IR injury is the primary cause of high mortality in acute renal insuffi ciency, the R-IR model in fi ghting against this injury is used in experimental studies widely.…”
Section: Introductionmentioning
confidence: 99%